Backdoor traders: illicit entrepreneurs and legitimate markets - Gounev, Philip Martinov (2011)
This dissertation examines the factors that determine the behaviour of criminal entrepreneurs in legitimate markets. The particular aspect studied is how such entrepreneurs enter a new market when they immigrate into a new country (Chapter 1). The empirical focus of the thesis is the Bulgarian illegal entrepreneurs involved in the sale of stolen cars. More specifically, the dissertation compares their market behaviour in Bulgaria and in Spain between the late 1990s and 2010. The empirical basis for the dissertation is a comprehensive analysis of summaries of 86 Spanish police investigations against organised crime networks, as well as fieldwork consisting of interviews with 79 offenders, law-enforcement officers, entrepreneurs, and car-dealers in Spain and Bulgaria (Chapter 2). To best understand the intertwining of criminal entrepreneurs and legitimate markets the thesis starts by examining the operations of the car markets in Spain and Bulgaria (Chapter 3). It goes on to explain the ‘car-theft industry’ – focusing on how criminal enterprises and networks are structured and operate (Chapter 4). The analysis then continues by comparing how stolen cars are sold by illegal entrepreneurs in Bulgaria and Spain, and the different ways in which ‘legal’ and ‘illegal’ markets intertwine (Chapter 5). The conclusion of this analysis is that Bulgarian criminal entrepreneurs failed to enter the market for used cars in Spain, and instead preferred to traffic and sell the stolen cars in Bulgaria. There are two sets of factors that explain the reasons behind this failure. The first one is the local socio-economic and historical legacies in Bulgaria, which explain how illegal entrepreneurs and buyers (typically part of local economic elites) are linked (Chapter 6), and the factors that fuel demand for stolen cars. The role of the Bulgarian immigrant community in Spain is also considered. The second set of factors, examined through the lenses of economic theories, includes the economic / business rationale that influences the illegal entrepreneurs’ behaviour when entering a market (Chapter 7). The thesis goes on to conclude (Chapter 8) that it is the first set, the complex socio-economic and historical factors that best explain the behaviour of criminal entrepreneurs and their failure to sell stolen cars in Spain